87. Utilization of Methicillin-Sensitive/Resistant Staphylococcus aureus Nares Screen to Decrease Vancomycin and Linezolid Use in Hospitalized Patients with Respiratory Infections - Zaidan, Noor F (Open Forum Infect Dis, 2020)
BACKGROUND: Pharmacist-driven protocols for utilization of methicillin-resistant Staphylococcus aureus (MRSA) nares screenings have shown to decrease duration of empiric gram-positive therapy and rates of acute kidney injury (AKI) in patients with respiratory infections. This study evaluated the impact of a pharmacist-driven MRSA nares screening protocol on duration of vancomycin or linezolid therapy (DT) in respiratory infections. METHODS: Patients aged 18 years and older with a medication order of vancomycin or linezolid for respiratory indication(s) were included. The MRSA nares screening protocol went into effect in October 2019. The protocol allowed pharmacists to order an MRSA nares polymerase chain reaction (PCR) for included patients, while the Antimicrobial Stewardship Program (ASP) made therapeutic recommendations for de-escalation of empiric gram-positive coverage based on negative MRSA nares screenings, if clinically appropriate. Data for the pre-intervention group was collected retrospectively for the months of October 2018 to March 2019. The post-intervention group data was collected prospectively for the months of October 2019 to March 2020. RESULTS: Ninety-seven patients were evaluated within both the pre-intervention group (n = 50) and post-intervention group (n = 57). Outcomes for DT (38.2 hours vs. 30.9 hours, P = 0.601) and AKI (20% vs. 14%, P = 0.4105) were not different before and after protocol implementation. A subgroup analysis revealed a significant reduction in DT within the pre- and post-MRSA PCR groups (38.2 hours vs. 24.8 hours, P = 0.0065) when pharmacist recommendations for de-escalation were accepted. CONCLUSION: A pharmacist-driven MRSA nares screening protocol did not affect the duration of gram-positive therapy for respiratory indications. However, there was a reduction in DT when pharmacist-driven recommendations were accepted. DISCLOSURES: All Authors: No reported disclosures